DREAM: an adaptive, randomised, placebo-controlled trial of duloxetine for reducing leg pain in people with chronic sciatica—trial protocol - Martin Underwood; Chung-Wei Christine Lin; Bethan Richards; Michael Dinh; Ralph Stanford; Christopher G Maher; Andrew J McLachlan; Thomas Lung; Peter Youssef; Laurent Billot; James McAuley; Giovanni E Ferreira; et al. (BMJ Open)
Introduction Sciatica is a debilitating condition that often becomes chronic, and for which there are few effective treatment options. Treatments such as the anti-depressant duloxetine have shown promise, but the evidence is inconclusive. We are describing a high quality, definitive trial to investigate the efficacy, safety and cost-effectiveness of duloxetine in chronic sciatica.Methods and analysis The duloxetine for chronic sciatica (DREAM) trial is a randomised, superiority, parallel-group, placebo-controlled, triple-blinded (participant, clinician, assessor) trial with an adaptive group sequential design investigating the efficacy and safety of duloxetine in participants with chronic sciatica of at least 3 months duration. Participants will be randomised at a 1:1 ratio to duloxetine or placebo. 332 participants will be recruited on presentation to general practices, specialist clinics and hospital emergency departments or from hospital in-patient wards and from the community. In the active treatment group, participants will receive duloxetine 60 mg per day for 12 weeks, including 1 week of titration at 30 mg/day. The treatment phase will be followed by a 2-week tapering phase where they will receive duloxetine 30 mg/day. Participants will be followed-up for 1 year, with outcomes being measured 4, 8, 12, 16, 26, and 52 weeks post-randomisation. The primary outcome is leg pain intensity at 12 weeks post-randomisation. Secondary outcomes include back pain intensity, disability, time to recovery, quality of life, depressive and anxiety symptoms, and sleep disturbance. Adverse events will be recorded, and a cost-effectiveness analysis will be conducted.Ethics and dissemination Ethical approval has been granted by the University of Sydney Human Research Ethics Committee. Trial results will be disseminated by publications, conference presentations and via the media.Trial registration number ACTRN12624000919516.